2014
DOI: 10.1016/j.jelectrocard.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Transtelephonic electrocardiography in the management of patients with acute coronary syndrome

Abstract: 10Background, purpose: The efficacy of the transtelephonic ECG system (TTECG) in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Transtelephonic electrocardiography (TTECG) was considered an effective answer to this challenge, and a national center with trained specialists was created in order to receive and analyze the records sent from rural areas to allow early diagnosis and treatment of myocardial infarction. TTECG involves the direct transmission of a locally recorded conventional ECG by telephone, which is decoded to a standard ECG on a computer in a cardiac center, where immediate professional ECG evaluation and interpretation is available 4 . The ECG is sent by telephone to the analysis center located in Santiago (the main metropolitan area of Chile), together with information about the patient including age, sex, relevant past medical history and chief complaint.…”
Section: Introductionmentioning
confidence: 99%
“…Transtelephonic electrocardiography (TTECG) was considered an effective answer to this challenge, and a national center with trained specialists was created in order to receive and analyze the records sent from rural areas to allow early diagnosis and treatment of myocardial infarction. TTECG involves the direct transmission of a locally recorded conventional ECG by telephone, which is decoded to a standard ECG on a computer in a cardiac center, where immediate professional ECG evaluation and interpretation is available 4 . The ECG is sent by telephone to the analysis center located in Santiago (the main metropolitan area of Chile), together with information about the patient including age, sex, relevant past medical history and chief complaint.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of pre-hospital ECG on the outcome of patients with ACS has been repeatedly confirmed in several recent studies reported from around the world [46][47][48][49], including China [50][51][52].…”
mentioning
confidence: 69%
“…Nemzetközi [10] és hazai viszonylatban is létezik jó gyakorlat eredményességéről szóló publikáció [11] a témában. A telemedicina ígéretes módszernek látszik akár aritmia, akár szívizominfarktus távdiagnosztikájában.…”
Section: Nemzetközi Ajánlások Születéseunclassified